The Limits of Contractual Freedom: Analyzing the Admissibility and Exceptions of Agreements Limiting or Excluding Tort Liability under French Civil Law - Mallet, Pierre; Nassar, Hala (Universitas Negeri Semarang, 2025)
Under French civil law, agreements that exclude or limit tort liability have traditionally been deemed null and void on grounds of public order, in stark contrast to the broad contractual freedom permitted in contractual liability. This paper examines the core legal question of when, if ever, such clauses may be valid, analyzing the narrow exceptions emerging in doctrine, jurisprudence, and, most significantly, the 2020 draft reform of French civil liability. The study identifies three key exceptions to the general prohibition: (1) clauses remain invalid in cases of gross negligence or intentional wrongdoing; (2) any exclusion or limitation of liability for bodily injury is categorically prohibited; and (3) consumer protection rules, particularly under EU-inspired unfair terms legislation, further restrict enforceability in B2C contexts. While current law maintains a rigid prohibition, the proposed reform (Articles 1284-1286) tentatively embraces the principle of validity, albeit confined largely to no-fault or vicarious liability scenarios, marking a pivotal shift toward aligning French law with comparative legal trends. The paper critically assesses this evolution, weighing the tension between contractual autonomy and the protective imperatives of tort law.